Modelling of Multi Factor Authentication System - L.P.Ramyasri, P; Malathi, D (International Journal of Engineering and Technology, 2018)
Authentication is a fundamental safeguard to access any information. A different type of authentication methods like single factor authentication method, two factor authentication method has been developed to improve userâ€™s security. Because of recent security attacks these methods are not reliable to provide better security. In this paper a multi-factor authentication framework is proposed that includes non-biometric authentication modalities like OTP, CAPTCHA, Graphical password, Textual Login. In this proposed framework users can randomly choose these authentication modalities. During login user interface time, failure verification count for each and every authentication modality is captured. A Feedback is collected fromÂ 20 userâ€™s and based on this time constraints, comparison of performance is done with respect to number of authentication modalities versus users interest. This proposed multi-factor authentication framework can be deployed in different levels of internet computing like email or social applications where user can randomly select authentication modalities based on time constraints.Â Â